Garde manger. - 4 0 16; Culinary Institute of America; 5 Culinary Institute of America (New York, 2007)
Composed Salads : Contrasting colors, flavors, texture, heights, and temperature all play a role in the arrangement of a composed salad. During this segment you will: practice techniques for preparing and presenting several kinds of composed salads ; receive tips for developing your own creations. Condiments : Condiments are the workhorse of garde manger{u2014}tart, spicy, or pungent, these items boost the flavor of any dish. In this segment, you will: learn the basic recipes for the five most commonly used condiments{u2014}mustard, ketchup, chutney, relish, and pickles ; explore variations on these recipes ; discover effective ways to use condiments in hors d'oeuvre and appetizers. Presenting Appetizers and Hors d'Oeuvre : In this essential training companion for anyone who handles garde manger functions, you will: discover the elegance of the first course ; study the key elements of successful appetizers{u2014}ingredient selection, presentation, and plating and service techniques.
DVD format.
Keywords: 2 -- 0; 6; Cookery (Cold dishes). -- 20; 20; 2